Analysis of The Effect of Perceived Price, Social Media Review, Brand Image, And Word of Mouth on The Re-Purchase Intention - Sari, Anindita Musthika; Mulia, Dipa (Dinasti International Journal of Management Science, 2025)
The purpose of this study is to understand the drivers underpinning repurchase intention by analyzing the influence of perceived price, social media review, brand image, and word of mouth on the repurchase intention of Pond's Age Miracle. In addition, the cognitive-affective attitude is explored as a mediating variable in this research, which encompasses consumers' rational assessments and emotional attachment to the product. This dual-process mechanism allows for further understanding of the implications of consumer perception and emotion concerning their purchasing behavior. A quantitative approach was adopted to analyze the relationships. Data were collected from 350 respondents who had previously bought or were at least considering buying Pond's Age Miracle. The Structural Equation Model was used to analyze the direct and indirect relationships between the variables, capturing a whole understanding of the associations. The results confirm that perceived price, social media reviews, brand image, and word of mouth are antecedents to consumer repurchase intention. More specifically, a strong brand image and favorable social media reviews enhance consumer trust and further encourage brand loyalty. Furthermore, word of mouth acts as an essential factor in influencing purchase decisions, as consumers are more likely to trust recommendations from peers before purchasing skincare products. Moreover, perceived price is important in this regard, as the consumer is looking for a product that is worthy in terms of price and quality. Cognitive-affective attitude is also an important mediating variable that underlines the influence of these factors on repurchase intention. Thus, consumers consider both logic, such as price and reviews, as well as emotional attachment to the brand, strengthening their intention to repurchase.